ANALISIS YURIDIS DAN PERSPEKTIF SYARIAH TERHADAP PRAKTIK PENANGKAPAN IKAN DESTRUKTIF DI MEDAN BELAWAN - Muhammad Yasir; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (SOSIOEDUKASI, 2025)
Fishing activities using trawl nets and seine nets (locally known as "pukat harimau") are still widely practiced in the waters of Medan Belawan, despite being officially banned by the government. This practice has led to severe damage to marine ecosystems, including seabed degradation, destruction of coral reefs, and the decline of juvenile fish populations. This raises serious concerns about the sustainability of fisheries and the livelihoods of coastal communities. In addition to positive legal approaches, a normative religious approach is needed to examine this phenomenon from the perspective of Islamic law. This study aims to analyze the use of trawl and seine nets from the perspective of Indonesian positive law and Islamic law, as well as to assess the effectiveness of the ban implementation among fishing communities in Medan Belawan District. The research uses a qualitative method with a combination of normative juridical and empirical approaches. Data were collected through document analysis, interviews, and direct field observation. The results show that although trawl fishing has been banned under Law No. 45 of 2009 and Ministerial Regulation No. 2 of 2015, the implementation at the local level faces various challenges. These include the fishermen’s economic dependency on high-yield fishing, lack of legal literacy, and limited understanding of Islamic values related to environmental protection. From an Islamic legal perspective, the use of destructive fishing gear is considered fasād fi al-arḍ (corruption on earth), violating the principles of khalīfah (stewardship), amānah (trust), and the prohibition of isrāf (excess). Thus, synergy between state law enforcement and Islamic-based educational approaches is necessary to promote a fair, sustainable, and sharia-compliant fishing practice.